Pengaruh Activity Ratio, Amil Fund Ratio, dan Growth Ratio terhadap Efisiensi Pengelolaan Dana Zakat pada Organisasi Pengelola Zakat di Indonesia - Hafizhan, Hilman; Sardiana, Anna (STIE Indonesia Banking School, 2024)
The purpose of this research is to measure the efficiecy of Zakat Management Organization to manage the zakah fund. And how the Activity Ratio, Amil Fund Ratio, and Growth Ratio affecting the efficiency of Zakat Management Organization. The population used in this research is the Zakat Management Orgnaizations that already operate in national scale and had publish their financial report at least in 2015-2018. Based on those population with purposive sampling method, there are 8 Zakat Management Organization that suitable as research sample. This research used Data Envelopment Analysis to generate the efficiency rate that Zakat Management Organizatoin had. And used Partial Least Square method to measure the ratios effect on Zakat Management Organizations’s efficieny. The result shows that average Zakat Management Organization is already had the maximum efficiency rate on 2015-2018, and had various efficiency rate each year. The result of Partial Least Square Analysis shows that there are positive effect on the three ratio towards Zakat Management Organization’s efficiency.